KEKERABATAN KOSA KATA BAHASA KARO, BAHASA NIAS, DAN BAHASA SIMALUNGUN DI KOTA MEDAN: KAJIAN LINGUISTIK HISTORIS KOMPARATIF - Sherly Novita; Dwi Widayanti (BAHAS, 2019)
Abstract  This article is entitled "The Lexical Kinship of Karo Language, Nias Language, and Simalungun Language in Medan City: Comparative Historical Linguistic Study". The research method used is a qualitative method. The methods and data collection techniques used are the method of referring to tapping, skillful, and recording techniques. The data analysis methods and techniques used are qualitative and quantitative methods with lexicostatistics techniques. In lexicostatistics, language kinship is seen based on the sound equations in the lexicon that appear in these languages. This phonetic resemblance will be the basis of whether a word in one language has a relationship with another language. The indicator used to determine the word kinship is a basic vocabulary called the basic Swadesh vocabulary which amounts to 200 vocabulary which is considered to exist in all languages in the world. The results of the study indicate that there was a kinship between the three languages. Keywords: kinship; Karo; Nias; Simalungun; lexicostatistics